038 Effect of dietary energy intake on nutrient utilization, performance, and maintenance requirements in late gestation cows and their calves. (1st February 2016) - Early, N. M.; Sawyer, J. E.; Trubenbach, L. A.; Boardman, C. J.; Baber, J. R.; Bell, N. L.; Wickersham, T. A.
Abstract: Drought and elevated land prices challenge the US cow-calf sector to meet increasing global beef demands via conventional, extensive methods. An alternative cow feeding and calving approach, accomplished in a controlled environment (i.e. drylot) was investigated using sixty, multiparous, late-gestation beef cows (461.5 kg initial BW). Cows (N = 60) were blocked by BW and individually fed one of four treatments (70, 85, 100, and 115% of NRC-predicted maintenance energy) in Calan gates for an average of 71 d before calving. Diets consisted of 2.00 kg of wheat straw (2.5% CP; 79% NDF) and four levels of a mixture of corn (45%), distiller's grain (42%) and premix (13%) fed at 2.70, 3.42, 4.12, and 4.85 kg/d to correspond with the 70, 85, 100, and 115% treatments. Following calving, pairs were managed as a group on pasture. Digestible energy intake increased linearly (11.84, 13.55, 15.53 and 17.71 Mcal/d for 70, 85, 100, and 115%; P < 0.01) per design; ME intake responded similarly (9.71, 11.11, 12.74 and 14.53 Mcal/d). No treatment differences ( P > 0.05) in digestibility were observed; DM digestibility averaged 62%. Cow retained energy over the duration of the study increased linearly ( P < 0.01) from 46.6 Mcal for 70% to 50.7, 106.3, and 123.8 Mcal for 85, 100, and 115%. Body weight gain increased linearly ( P < 0.01) from 0.7 kg for 70% to 3.6, 17.7, and 24.2 kg for 85, 100, and 115%. Calf birth weight increased linearly ( P = 0.01) from 32.5 kg for 70% to 35.5, 35.2, and 36.8 kg for 85, 100, and 115%. There were no differences ( P > 0.05) in cow or calf body weights among treatments at 60, 90, 120 or 160 days post parturition. Brix (%) values of cow colostrum at parturition did not differ ( P > 0.05). Immunoglobulin G levels in calf serum collected 24 h after birth did not differ ( P > 0.05). No differences ( P > 0.05) in postpartum interval were observed. Production goals of the cow-calf sector can be successfully met by limit feeding late-gestation beef cows in a drylot setting at levels at least 70% of NRC-predicted energy requirements for maintenance.